The Effectiveness of Blended Education in Educational Institutions - Salomova, Ra’no Vassievna (ASEAN Journal of Educational Research and Technology, 2025)
Digital educational resources, as the most crucial element of blended learning, enable the organization of non-linear development of learning materials, taking into account students' characteristics. The role and significance of modern teaching methods - interactive approaches and innovative technologies - in the educational process is immeasurable. To determine the level of development of students' pedagogical competence through the implementation of a blended learning system in the educational process, 66 students were involved in the experimental field. Of these, 34 participated in the experimental group and 32 in the control group. Various methods of knowledge assessment were employed in the experimental work: questionnaires, interviews, discussions, and tests.